Customer Experience and Branding Strategies for Enhancing Loyalty and Their Impact on Beauty Product Purchasing Decisions Among Consumers in West Java - Evaf Maulina; Zakeus Dadi; Andri Ardhiyansyah; Yanti Susanti (West Science Business and Management, 2026)
The rapid growth of the beauty industry in Indonesia has intensified competition among brands, requiring companies to focus on customer-oriented strategies to enhance consumer loyalty and purchasing behavior. This study aims to examine the effects of customer experience and branding strategies on customer loyalty and their impact on beauty product purchase decisions among consumers in West Java. A quantitative research approach was employed using a survey method. Data were collected from 200 respondents who had purchased beauty products within the last six months through a structured questionnaire measured using a five-point Likert scale. The sampling technique utilized purposive sampling. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results indicate that customer experience has a positive and significant effect on customer loyalty, while branding strategies also positively and significantly influence customer loyalty. Furthermore, customer experience, branding strategies, and customer loyalty significantly affect purchase decisions. The mediation analysis reveals that customer loyalty significantly mediates the relationships between customer experience and purchase decisions as well as between branding strategies and purchase decisions. The structural model demonstrates strong explanatory power, with R² values of 0.648 for customer loyalty and 0.732 for purchase decisions. These findings suggest that enhancing customer experience and implementing effective branding strategies can strengthen customer loyalty and encourage consumers to make purchasing decisions. This study contributes to the consumer behavior and marketing literature by providing empirical evidence regarding the interconnected roles of customer experience, branding strategies, customer loyalty, and purchase decisions in the beauty product industry.